A sodium borohydride hydrogen generation reactor for stationary applications: Experimental and reactor simulation studies - Sousa, T. (2013)
Ruthenium on nickel-foam catalyst was prepared for hydrogen production from the hydrolysis reaction of an alkaline NaBH4 solution. Experiments were carried out at five temperatures (30, 40, 45, 50 and 60 °C) in a 0.1 dm3 small batch reactor. To understand the kinetic behaviour of the hydrolysis reaction in the presence of this catalyst, the experimental data were fitted to three kinetic models (zero-order, first-order and Langmuir–Hinshelwood) using the integral method. Results showed that Langmuir–Hinshelwood model described fairly well the reaction for all tested temperatures and for the entire time range. Zero-order could be applied only at low temperatures or until the concentration of NaBH4 remained high in the solution; first-order could be only applied efficiently at 60 °C. In addition to the kinetic study, a dynamic, three dimensional and non-isothermal model was developed to describe a pilot scale reactor for stationary use. The experimental data was used to validate the numerical model which was developed using a commercial solver software. All relevant transport phenomena were treated in detail and the kinetic model developed previously was introduced into the algorithm. Results showed that the reaction rate was extremely affected by the mass transport resistance of sodium borohydride from the bulk to the catalyst surface.